Pain assessment of elderly with neurocognitive disorders in long-term care: an occupational lens. (30th September 2020) - Ruest, M; Léonard, G; Lagueux, E; Boissy, P; Milot, M H; Bourbonnais, A; Guay, M
Abstract: Background: Occupational performance of older adults living in long-term care facilities is influenced by environmental possibilities and service provision. Pain among older adults with neurocognitive disorders might be a factor mitigating functional status. However, pain evaluation during daily routine through advanced stages of the disorder is scarce. Objective: Identify pain-related behaviors of older adults with neurocognitive disorders during their morning routine in long-term care facilities. Methods: A multiple-case study based on an embedded concurrent mixed methods design (quan-QUAL) was conducted in Quebec (Canada) in three long-term care units. Older adults with a neurocognitive disorder were observed (from 7:00 to 12:00 AM) and evaluated through the accomplishment of their morning routine. Through inter- and intra-case analyses, pain assessment scales (PACSLAC-II, Algoplus and DS-DAT) and morning routine assessment (occupational therapist's observations of the person, occupations and environment, functional autonomy measure, field notes) were integrated in mixed methods matrixes. Results: Sixteen (n = 16) participants (average age: 76 years old [59, 93]) with various but advanced functional declines and pain symptoms were included. Participants' significant occupations all related to basic activities of daily living. Hygiene care and getting dressed were occupations for which an alteration of occupational performance was identified. Conclusions: During their morning routine, older adults with a neurocognitive disorder living in long-term care facilities are facing pain symptoms and occupational deprivation, limiting the fulfilment of their needs and their engagement in occupations. Accordingly, older adults' occupations in relation to their environment should also be considered in future studies investigating pain. Key messages: Occupational performance of older adults with a neurocognitive disorder living in long term care facilities is limited to basic activities of daily living. Assessment of pain of patients with a neurocognitive disorder in long-term care units should include the identification of environmental and occupational factors contributing to this pain.